Age, gender, and education are associated with cognitive performance in an older Israeli sample with type 2 diabetes. (8th August 2013) - Guerrero‐Berroa, Elizabeth; Ravona‐Springer, Ramit; Schmeidler, James; Silverman, Jeremy M.; Sano, Mary; Koifmann, Keren; Preiss, Rachel; Hoffman, Hadas; Heymann, Anthony; Schnaider Beeri, Michal
<x xml:space="preserve">Abstract</x> Objective To evaluate the relationships of age, education, and gender with performance on neuropsychological tests in a cognitively intact, older Israeli sample with type 2 diabetes (T2D). Methods We examined 862 participants, 65–84 years old, enrolled in the Israel Diabetes and Cognitive Decline study. Multiple regression assessed associations of performance on 17 neuropsychological tests, including the Consortium to Establish a Registry for Alzheimer's Disease neuropsychological battery, with age, education, and gender. Results Higher education and younger age were consistently associated with better performance. Women outperformed men on all memory tasks; men outperformed women on two non‐verbal measures. These patterns of demographic associations with cognitive performance were very similar to those of US cohorts. Conclusions In a cognitively intact, older Israeli sample with T2D, better test performance is associated primarily with higher education, followed by younger age and gender differences. Although T2D is associated with cognitive deficits, it recapitulates the patterns of relationships between cognitive performance and demographic characteristics seen in non‐T2D diabetic samples. Copyright © 2013 John Wiley & Sons, Ltd.